Developing materials for teaching translation - Sri Endah Tabiati; Yana Shanti Manipuspika (Jurnal Linguistik Terapan, 2018)
In teaching translation we can use authentic materials to be translated by the students. This is done for translating practice. However, prior to translating we have to explain to the students translations theories as the basis to guide the translation work in order that the students are able to produce the target language well. Based on the experience in teaching translation at the university, we have published a book called “Translation: Theory and Practice”. In writing the book, we refer to the opinions of translation experts documented in books and articles. We also cited reseach results whether they are published or unpublished. The book has been printed twice, in February 2017 and in September 2017. To evaluate the book, we distributed questionnaire students who have used the book to get feedbacks for improving the book in the coming edition. This paper aims to share the contents of the book and the students’ opinions about the book.